IT Teachers’ Experience of Teaching–Learning Strategies to Promote Critical Thinking - Bailey, Roxanne; Mentz, Elsa (Issues in informing science & information technology education, 2015)
Information Technology (IT) high school learners are constantly struggling to cope with the challenges of succeeding in the subject. IT teachers, therefore, need to be empowered to utilize appropriate teaching–learning strategies to improve IT learners’ success in the subject. By promoting critical thinking skills, IT learners have the opportunity to achieve greater success in the most difficult part of the curriculum, which is programming. Participating IT teachers received once-off face-to-face professional development where some teachers received professional development in critical thinking strategies while other IT teachers received professional development in critical thinking strategies infused into pair programming. To determine how teachers experience these suggested strategies, teachers participated in initial interviews as well as follow-up interviews after they had implemented the suggested strategies. From the interviews, it became evident that teachers felt that their learners benefited from the strategies. Teachers in the pair programming infusing critical thinking strategies focused more on the pair programming implementation than on the totality of pair programming infused with critical thinking. Although teachers were initially willing to change their ways, they were not always willing to implement new teaching–learning strategies.